Brill's companion to Cicero : oratory and rhetoric - May, James M. (Brill's Companions to Classical Studies., 2002)
This volume is intended as a companion to the study of Cicero's oratory and rhetoric for both students and experts in the field: for the neophyte, it provides a starting point; for the veteran Ciceronian scholar, a place for renewing the dialogue about issues concerning Ciceronian oratory and rhetoric; for all, a site of engagement at various levels with Ciceronian scholarship and bibliography. The book is arranged along roughly chronological lines and covers most aspects of Cicero's oratory and rhetoric. The particular strength of this companion resides in the individual, often very original approach to sundry topics by an array of impressive contributors, all of whom have spent large portions of their careers concentrating upon the oratorical and rhetorical oeuvre of Cicero. A bibliography of relevant items from the past 25 years, keyed to specific Ciceronian works, completes the volume. Brill's Companion to Cicero will become the standard reference work on Cicero for many years.